Nitrogen Isotope Sclerochronology—Insights Into Coastal Environmental Conditions and Pinna nobilis Ecology - Peharda, Melita; Gillikin, David P.; Schöne, Bernd R.; Verheyden, Anouk; Uvanović, Hana; Markulin, Krešimir; Šarić, Tomislav; Janeković, Ivica; Župan, Ivan (Frontiers in Marine Science, 2022)
Pinna nobilis is a large bivalve endemic to the Mediterranean Sea that lives in shallow coastal areas. Due to its size and relatively fast shell growth rates, it is an interesting taxon for high-resolution study of nitrogen isotopes of carbonate bound organic matter (δ15NCBOM). In this study we tested if P. nobilis shells can be used as an indicator of the nitrogen isotope baseline of the system, if it can provide high-resolution data on environmental δ15N variability, and if the chemical properties of the shell and biomineralization process change in response to mass mortality events spreading in the Mediterranean. Shells were opportunistically collected during 2019 and 2020 by skin diving, as a part of a project on mortality monitoring, from four shallow coastal localities in the eastern Adriatic. Shell powder for δ15NCBOM analysis was collected by milling sample swaths from the internal (low-resolution) and external (high resolution) shell surface. Significant differences in δ15NCBOM, obtained from the internal shell surface, were observed between sampling localities with different anthropogenic influences, with lowest values ( 3-4‰) recorded for shells obtained from Pag Bay, and highest ( 6-8‰) for shells sampled in Lim and Kaštela Bays. High-resolution samples from the external shell surface of Pinna nobilis showed spatial and temporal variations in δ15NCBOM values, with temporal resolution of 1-3 weeks. High-resolution δ15NCBOM data obtained from the shell Kas1 corresponded to a time interval from spring 2018 to summer 2019 and had a pronounced increase of δ15NCBOM values closest to the shell margin coupled with a decrease in δ13Cshell values, indicating that this animal was experiencing stressful conditions several months prior to its death. According to our findings, δ15NCBOM values from P. nobilis shells can serve as an indicator of the isotopic baseline of the ecosystem potentially as a powerful tool to study bivalve physiology.